PENGARUH KETERAMPILAN KOMUNIKASI TERHADAP HASIL BELAJAR MATA PELAJARAN BAHASA INDONESIA KELAS IV DI MI RADEN BAGUS TALOK - Hikmatul Amalia Nahdlia; Ika Ratih Sulistiani; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
Communication is very important for teachers in conveying learning to students, and without communication learning will not succeed. Because the success of learning is determined by the teacher, so a teacher must have communication skills. Communication in education can improve student learning outcomes because teacher-student communication is one of the external factors that can affect student learning outcomes. However, here the researchers found several problems related to communication in the teaching and learning process that occurred at MI Raden Bagus which were not in accordance with ideal conditions. This can be seen when the teacher in teaching is only fixated on the delivery of what is in the textbook and the lack of preparation and mastery of the material so that in explaining it is not clear and difficult for students to understand. Lack of teacher communication skills in this learning process which ultimately has an impact on low learning outcomes. In this study, researchers conducted research at MI Raden BagusTalok using the saturated sampling quantitative research method. Data collection techniques are questionnaires, tests, and documentation. The results of the study indicate that there is a significant influence between communication skills on student learning outcomes. Keyword: Communication Skills, Learning Outcomes